PENGARUH MODEL KOOPERATIF TIPE JIGSAW DIDUKUNG MEDIA VISUAL TERHADAP KEMAMPUAN MENGIDENTIFIKASI DAMPAK PERISTIWA ALAM KELAS V SDN SONOPATIK 1 KABUPATEN NGANJUK - ANDAYANI, SARI FATUL; LAILA, ALFI (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2015)
The aim of the research is: 1) determine the influence of usage conventional model supported visual media to the ability to identify impact natural events in grade V SDN Sonopatik 1, Sub-district Berbek Kediri Regency. 2) determine the influence of usage cooperativemodel types jigsawsupported visual media to the ability to identify impact natural events in grade V SDN Sonopatik 1, Sub-district Berbek Kediri Regency. 3) knowing the difference between the effect of the use of cooperativemodel types jigsawsupported visual media with convensional model supported visual media to the ability to identify impact natural events in grade V SDN Sonopatik 1, Sub-district Berbek Kediri Regency.This Research typesTrue Experimental (Pretest-Posttest Control Group Design).  Use approach quantitative with subjectsgrade V SDN Sonopatik 1 sub-districts Berbek, Nganjuk Regency.data collection instrumens used is a objective test. The results of the research showed that (1) conventional model supported visual media  effect is very significant impact to the ability to identify natural events, this is proven with value of tcount (4.580) >ttable (2.819) and thoroughness classical reached 53,48%. (2) cooperativemodel typesjigsaw supported media visual effect is very significant impact to the ability to identify natural events, this is proven with value of  tcount (9.700) >ttable (2.807) and thoroughness classical reached 78,75%. (3) cooperative model typesjigsawsupported visual media superior than conventional model supported visual media.